Modal Sosial Komunitas Sekolah Kaki Langit dalam Membina Anak di Bonto Manai Kabupaten Maros - Marisal Marisal; Andi Agustang; Najamuddin Najamuddin (Universitas Negeri Makassar, 2022)
The purpose of the study was to describe the Social Capital of the Sky Sky School Community in Conducting Coaching and the obstacles to the Sky Sky school community in conducting coaching. Analyzed using a sociological perspective. This study uses descriptive qualitative, the determination of informants using the purposive sampling technique with the criteria for the daily management of the Kaki Langit School. Collecting data using observation, interviews and documentation. Data analysis by organizing data, processing data and drawing conclusions. Validation of the data used is source triangulation. The results showed: (1) the social capital of the Kaki Langit community is volunteers having education at the undergraduate, student, and high school levels who have patience, blend in youth, motivator, learn while playing, art, religion and provide a reading garden. Community members want to provide guidance when they see the children there are very enthusiastic about learning even though their limitations are less supportive in accessing education, when compared to other areas. (2) the obstacles to the Skyscraper school community in conducting coaching are telecommunications networks, road access, electricity, when the volunteers coincide with other activities, children are difficult to control and at first they are shy and quiet.